Road traffic and adverse respiratory effects in children. SIDRIA Collaborative Group. Issue 11 (November 1998) - Ciccone, G; Forastiere, F; Agabiti, N; Biggeri, A; Bisanti, L; Chellini, E; Corbo, G; Dell'Orco, V; Dalmasso, P; Volante, T F; Galassi, C; Piffer, S; et al.
Abstract : OBJECTIVES: To investigate the relation between traffic indicators in the area of residence and the occurrence of chronic respiratory disorders in children. METHODS: A population based survey was conducted in 10 areas of northern and central Italy (autumn 1994 to winter 1995) in two age groups (6-7 and 13-14 years). Information on several respiratory disorders and on traffic near residences was collected with a questionnaire given to children and to their parents. The sample analysed included 39, 275 subjects (response rate 94.4%). Outcomes were: (a) early (first 2 years of life) respiratory diseases, and (b) current respiratory disorders (asthma, wheeze, cough, or phlegm in the past year). Odds ratios (ORs) and 95% confidence intervals (95% CIs), adjusted for several potential confounders, were estimated from logistic regression models. Main results were stratified by level of urbanisation (metropolitan areas, other centres). RESULTS: In the metropolitan areas, high frequency of lorry traffic in the street of residence was associated with significantly increased risks for many adverse respiratory outcomes. Among early respiratory diseases, the strongest associations were found for recurrent bronchitis (OR 1.69, 95% CI 1.24 to 2.30), bronchiolitis (1.74, 1.09 to 2.77) and pneumonia (1.84, 1.27 to 2.65), although no association was detected for episodes of wheezing bronchitis. All the current respiratory disorders were positively and consistently associated with frequency of lorry traffic, particularly the most severe bronchitic and wheezing symptoms: persistent phelgm for > 2 months (1.68; 1.14 to 2.48), and severe wheeze limiting speech (1.86; 1.26 to 2.73). No or weaker associations with heavy vehicular traffic were detected in urban and rural areas and no increased risks were found in the whole sample with the reported traffic density in the zone of residence. After extensive evaluations, the potential of reporting bias seems unlikely. CONCLUSION: Exposure to exhausts from heavy vehicular traffic may have several adverse effects on respiratory health of children living in metropolitan areas, increasing the occurrence of lower respiratory tract infections early in life and of wheezing and bronchitic symptoms at school age.